La legge n. 194 del 1978 fra adeguamenti scientifici, obiezione di coscienza e battaglie ideologiche (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The essay focuses on the most recent issues of the debate that still surrounds the l. n. 194 of 1978, forty years after its approval. The analysis involves declarations of gynecologists, public bodies (e.g. Lombardy Region) or prominent personalities in the world of culture, against abortion, as well as the phenomenon of the increasing number of conscientious objectors. The A. proposes a method where the conflicts between rights of mothers and the ones of fetuses are solved with the technique of constitutional balance and not for ideological purposes.
Keywords: Abortion; scientific innovation; conscientious objection; constitutional balance; ideological choice